PENGARUH AKUNTABILITAS, PENGETAHUAN AUDIT DAN GENDER TERHADAP KUALITAS HASIL KERJA AUDITOR INTERNAL (Studi Empiris Pada Inspektorat Wilayah Provinsi DKI Jakarta) - Ainia Salsabila; Hepi Prayudiawan (Program Magister Akuntansi Unsyiah, 2011)
This research examines the influence of accountability, audit knowledge, and gender to quality of work of internal auditors. The respondents in this study were auditors who worked for The Inspectorate of DKI Jakarta Province. The number of auditor who observed in this study was 68 auditors. They came from some auditors who worked in The Inspectorate of DKI Jakarta Province. The method of determining the sample was purposive sampling method, the data processing methods. That used by researcher were the multiple regression analysis.The result shows that the accountability, audit knowledge and gender simultaneously and significantly to quality of work of internal auditors. Keyword: accountability, audit knowledge, gender, quality of work of internal auditor.